Ultrasensitive detection of site-specific DNA methylation by loop-mediated isothermal amplification. Issue 27 (28th June 2016) - Wen, Hui; Wang, Hui; Wang, Honghong; Yan, Jingli; Tian, Hui; Li, Zhengping
Abstract : A novel LAMP-based methylation assay for simple, robust and cost-effective detection of site-specific DNA methylation has been developed. Abstract : A novel loop-mediated isothermal amplification (LAMP)-based methylation assay for simple, robust and cost-effective detection of site-specific DNA methylation has been developed. DNA targets are first treated with methylation-sensitive restriction endonuclease (HpaII), where the DNA targets will be cleaved at specific unmethylated-cytosine residues while leaving the methylated DNA intact. Subsequently, the methylated DNA targets can serve as templates to perform LAMP for the detection of DNA methylation with real-time fluorescence measurements by using a common fluorescent dye (SYBR Green I). Taking advantage of the simplicity and high specificity of HpaII digestion and the isothermal nature and high sensitivity of LAMP, the proposed assay can greatly simplify the detection of DNA methylation and achieve ultrahigh sensitivity and specificity. With this assay, as low as 10 aM methylated DNA can be detected and 0.1% methylated DNA can be determined in the presence of a large excess of unmethylated DNA.